EVALUATION OF PERFORMANCE OF COMPOSITE FILLING MATERIALS IN RESTORATION OF PERMANENT TEETH IN CHILDREN - L.F. Kaskova; N.V. Yanko; O.O. Kulai (Український стоматологічний альманах, 2021)
A paradigm shift in dental caries treatment in paediatric dentistry is viewed towards a wide using of composite resins. This prospective clinical trial are evaluated and compared during 18 months of clinical performance of a microhybrid composite with a nanoceramic resin composite placed in сlass I and II cavities in permanent teeth in children.